Studies on survival of Xanthomonas campestris pv. glycines - M.N. KHARE, U.K. KHARE and (Indian Phytopathology, 2002)
Soybean (Glycine max (L.) Merrill.) suffers due to several plant pathogens, of which, Xanthomonas campestris pv. glycines (Nakano) Dye, 1980, causing bacterial pustule disease is the most serious one. Bakavea reported that the bacterium over winters on plant debris in the soil. The bacterium was found to remain viable in dry diseased leaves as well as partially decayed leaves of soybean. Survival of the bacterium is favoured when soybean debris is kept on the soil surface rather than incorporated in soil.